GHANA’S URBAN INFORMAL SECTOR: PERCEPTIONS, ATTITUDES AND CHALLENGES - AMOAH, MARY (IJRDO - Journal of Business Management, 2015)
There is a rising interest in the informal sector the world all over emanating from the reality that the sector houses a greater share of the active labour force. The informal sector of Ghana’s economy is estimated to provide employment for approximately 80% of the active workforce. After over 50 years of independence, Ghana is struggling to grow and transform its informal sector as it still operates on rudimentary methods making the future very precarious. The study adopted the qualitative approach and sought to examine the perceptions, attitude as well as the realities and challenges of the urban informal sector with the Ghana National Association of Garages (GNAG) and the National Association of Beauticians and Hair Dressers as a case study (NABH). Findings of the study indicated that, the urban informal sectors absolves the academically weak or people who perceive themselves as weak academically. Perception amongst the urban informal sector is that, formal sector employment is rewarding than informal sector employment, operators don’t see themselves as entrepreneurs and commits a lot of errors in their operations. This explains some of the reasons for the stunted growth and the limited transformation experienced in the sector. However, there is still hope or the sector if efforts are made to regularize the sector through the data capturing, encouraging the formation of vibrant and registered associations, reorientation of the perception of the operators through capacity building and training whilst creating the necessary conducive micro and macroeconomic environment for their operation.